Perlindungan Hukum Bagi Anak Sebagai Saksi dalam Pemeriksaan Perkara Pidana - Asmadi, Erwin (Iuris Studia: Jurnal Kajian Hukum, 2020)
Law No. 11 of 2012 concerning the Juvenile Justice System explains that children have a strategic role which is explicitly stated that the state guarantees the rights of every child to survival, growth and development as well as protection from violence and discrimination. Therefore, the best interests of children should be lived out as the best interests for the survival of mankind. Law No. 23 of 2002 concerning Child Protection, explicitly explains in Article 1 Paragraph (2),